Innovation in the Use of Artificial Intelligence in Improving Learning Motivation in Student Final Project Completion: Inovasi Penggunaan Artificial Intelligence dalam Meningkatkan Motivasi Belajar Pada Penyelesaian Tugas Akhir Mahasiswa - Ningtyas, Ananta Sany; Yetri , Yetri; Wiliyanti, Vandan (Indonesian Journal of Innovation Studies, 2025)
General Background: The integration of Artificial Intelligence (AI) into education is transforming how students engage with academic tasks. Specific Background: With the growing accessibility of AI tools such as ChatGPT, Grammarly, and QuillBot, students increasingly utilize these platforms in academic writing, particularly when completing final assignments. Knowledge Gap: However, limited empirical evidence exists regarding the impact of AI usage on students’ learning motivation. Aims: This study investigates how the innovative use of AI contributes to enhancing students’ motivation in completing final assignments. Method: Employing a quantitative descriptive-correlational design, data were collected from 507 students across eight study programs at the Faculty of Tarbiyah and Teacher Training, UIN Raden Intan Lampung, selected via purposive sampling. A five-point Likert scale questionnaire was used, with data analyzed using the Orange Data Mining application through box plot visualizations and ANOVA tests. Results: The findings indicate a positive correlation between the intensity of AI usage and students’ learning motivation. Novelty: This study provides one of the first quantitative insights into the motivational effects of AI tools in higher education settings. Implications: The results offer valuable input for educational institutions in designing AI-integrated learning strategies that foster student motivation and academic engagement. Highlights: Highlights a positive correlation between AI use and student motivation. Uses data-driven analysis with Orange Data Mining and ANOVA. Offers practical insights for AI-integrated learning strategies. Keywords: Artificial Intelligence, Learning Motivation, Final Assignment, Higher Education, Educational Technology